Investigation of complement system activation and regulation during Indian Antarctic expedition - Bhushan, Brij; Tanwar, Himanshi; Dogra, Vikas; Singh, Shashi Bala; Ganju, Lilly (Polar Science, 2021)
Antarctica is one of the most effective sites to measure the impact of human isolation, sleep deprivation, light-dark period and harsh environmental conditions. In the present study we address several aspects of the activation and regulation of the complement system. Alterations in the body systems mainly related to immunology, physiology and psychology, during expeditions to the Antarctica, leads to various complexities. In the present study the research findings are based on two group members from 34th Indian Scientific Expedition to the Antarctic. The first group-included members from “summer” expedition, while the second group-included members subjected to the Antarctic environment for the “winter” expedition. Blood samples were collected from both the groups and evaluated for various activation and regulatory complement protein. Serum levels of C3, C4 & C5a were analysed. Anaphylatoxin C3a was up regulated significantly in both the teams. However, C5a, another anaphylatoxin was also increased in both teams though not significantly during winter expedition. Complement regulatory proteins C1- Inhibitor, Factor D, Factor H were unregulated significantly during summer and winter exposures. However, Factor D levels increased significantly only in the month of April (W2) of summer exposure. Thus, this indicates that harsh Antarctic conditions could be detrimental factor for activation of complement system in both the teams. However, the effect of activated complement system during the expedition was regulated in positive manner and could not be correlated with clinical manifestations due to the multiple stressors and small population size during Antarctic expedition. journal article